Penerapan Model Pembelajaran Koperative Tipe Jigsaw untuk Meningkatkan Hasil Belajar Materi Bilangan Kompleks pada Siswa XI SMA Nurul Jadid Semester Ganjil Tahun 2024/2025 - Azizi, Muhammad Alaika Nashrul; Hidayati, Arini; Illah, Ata (Papanda, 2025)
This study aims to improve students’ mathematics learning outcomes on the topic of Complex Numbers through the implementation of the Jigsaw cooperative learning model in Class XI of SMA Nurul Jadid during the first semester of the 2024/2025 academic year. The study was motivated by students’ low understanding and interest in mathematics, which resulted from conventional teaching methods that lacked student engagement. The Jigsaw model was selected because it emphasizes collaboration, individual responsibility, and active participation. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of the study were 15 students of class XI MIPA 1. Data were collected through learning outcome tests and student activity observations, then analyzed descriptively. The findings show a significant improvement from Cycle I to Cycle II. The average student score increased from 61.3 to 91.3, while classical mastery rose from 53% to 93%. In addition, students demonstrated more active and collaborative learning behavior. The Jigsaw model proved effective in creating an interactive learning environment, enhancing motivation, and deepening conceptual understanding in mathematics. Therefore, the Jigsaw cooperative learning model is recommended as an effective strategy for improving learning outcomes and the quality of mathematics instruction in secondary schools.